Persistence of Immunity Following 2-Dose Priming with a 10-Valent Pneumococcal Conjugate Vaccine at 6 and 10 Weeks or 6 and 14 Weeks of Age in Nepalese Toddlers. Issue 10 (20th July 2021) - Gurung, Meeru; Bijukchhe, Sanjeev M.; Hariri, Parisa; Voysey, Merryn; Kandasamy, Rama; Thorson, Stephen; Maskey, Pratistha; Pandit, Raju; Shrestha, Biplav; Gautam, Madhav Chandra; Maharjan, Mamata; Lama, Laxmi; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The pneumococcal conjugate vaccine has had a substantial impact on invasive pneumococcal disease. Previously, we compared immunity following vaccination with the 10-valent pneumococcal conjugate vaccine (PCV10) administered at 2 slightly different schedules: at 6 and 10 weeks of age, and at 6 and 14 weeks of age, both followed by a 9-month booster. In this study, we followed up those participants to evaluate the medium-term persistence of serotype-specific pneumococcal immunity at 2-3 years of age. Method: Children from the previous studies were contacted and after taking informed consent from their parents, blood samples and nasopharyngeal swabs were collected. Serotype-specific IgG antibody concentrations were determined by enzyme-linked immunosorbent assay, for the 10 vaccine serotypes, at a WHO pneumococcal serology reference laboratory. Findings: Two hundred twenty of the 287 children who completed the primary study returned at 2–3 years of age to provide a blood sample and nasopharyngeal swab. The nasopharyngeal carriage rate of PCV10 serotypes in the 6 + 14 group was higher than the 6 + 10 group (13.4% vs. 1.9%). Nevertheless, the proportion of toddlers with serum pneumococcal serotype-specific IgG greater than or equal to 0.35 µg/mL was comparable for all PCV10 serotypes between the 6 + 10 week and 6 + 14 week groups. Similarly, the geometric mean concentrations of serum pneumococcal serotype-specific IgG levels were similar in the 2 groups for all serotypes, except for serotype 19F which was 32% lower in the 6 + 10 group than the 6 + 14 group. Conclusion: Immunization with PCV10 at 6 + 10 weeks or 6 + 14 weeks, with a booster at 9 months in each case, results in similar persistence of serotype-specific antibody at 2-3 years of age. Thus, protection from pneumococcal disease is expected to be similar when either schedule is used.